2017
DOI: 10.18632/oncotarget.21911
|View full text |Cite
|
Sign up to set email alerts
|

Dietary folate levels alter the kinetics and molecular mechanism of prostate cancer recurrence in the CWR22 model

Abstract: Folate impacts the genome and epigenome by feeding into one-carbon metabolism to produce critical metabolites, deoxythymidine monophosphate and s-adenosylmethionine. The impact of folate exposure and intervention timing on cancer progression remains controversial. Due to polyamine metabolism’s extraordinary biosynthetic flux in prostate cancer (CaP) we demonstrated androgen stimulated CaP is susceptible to dietary folate deficiency. We hypothesized dietary folate levels may also affect castration recurrent CaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Since our previous data revealed that AHR controls polyamine biosynthesis, we decided to assess the degree to which polyamine biosynthesis gene expression correlates with patient survival. To this end, we created a polyamine biosynthesis score by summing the expression levels of the signature enzymes for polyamine biosynthesis (AZIN1, OAZ1, OAZ2, ODC1, SMS, SRM, and AMD1) as previously described for a different gene expression set (89). We analyzed patient survival in relation to this score.…”
Section: Resultsmentioning
confidence: 99%
“…Since our previous data revealed that AHR controls polyamine biosynthesis, we decided to assess the degree to which polyamine biosynthesis gene expression correlates with patient survival. To this end, we created a polyamine biosynthesis score by summing the expression levels of the signature enzymes for polyamine biosynthesis (AZIN1, OAZ1, OAZ2, ODC1, SMS, SRM, and AMD1) as previously described for a different gene expression set (89). We analyzed patient survival in relation to this score.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work revealed that prostate cancer (CaP) is exquisitely sensitive to perturbation of polyamine metabolism and connected pathways due to high polyamine metabolic flux [9][10][11]13 . These studies demonstrated that the prostate relies heavily on the methionine salvage pathway to survive and that MTAP inhibition blocks LNCaP xenograft growth when given at the time of xenograft implantation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-performance liquid chromatography for polyamines. Ultra-Performance liquid chromatography analyses for polyamines were carried out similarly to previously described methods [10][11][12][13] with adjustments made to the flow rate, gradient, and column indicated below. Acetylated polyamines were extracted from media as previously described 10 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations